Maturation of human early-minted blood antibody-secreting cells is coupled with increased IgG secretion rates - Nguyen, Doan C.; Hentenaar, Ian T.; Cabrera-Mora, Monica; Kyu, Shuya; Morrison-Porter, Andrea; Haddad, Natalie S.; Andrews, Joel; Roberts, Danielle; Lonial, Sagar; Sanz, Ignacio; Lee, F. Eun-Hyung (Frontiers in Immunology, 2025)
Plasma cells are known antibody-secreting factories with immunoglobulin (Ig) transcripts that increase as the cell matures into a long-lived plasma cell (LLPC) in the bone marrow (BM). Whether the Ig secretion rates among human antibody-secreting cells (ASC) are homogeneous or BM LLPC are capable of secreting more antibodies per cell compared to early-minted blood ASC remain unclear. Here, we use bulk and single cell cultures in a novel in vitro BM mimetic survival system to measure the IgG secretion rates of human ASC. We find that the mature BM ASC produce more IgG molecules per cell compared to immature, early-minted blood ASC. Furthermore, these blood ASC can mature into LLPC phenotypes in culture, and we show that ASC on day 7 secrete more IgG per cell than the input ASC from day 0. Thus, as human ASC mature, they increase the number of Ig transcripts and result in higher Ig secretion. These results also demonstrate that the mature ASC in the BM have higher Ig secretion rates compared to early-minted blood ASC.